New empirical formula for reduction factor of head garment / \c Muhammad Aiman bin Ahmad Fozi. - Muhammad Aiman Ahmad Fozi (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2017)
This study focused on pressure therapy treatment at facial area of the head segment. Hence, only the face area was subjected for the pressure performances and area opening area such as eyes, nose and mouth were not being measured for the pressure. Due to the challenge of having real patient with facial scars from burn injury, uninjured human was used as a subject. The scope of this study is to develop the fabrication method of HG using digital design approach to obtain optimum pressure outputs.The development of the HG mainly focus on the pressure performances. The effect of the time taken for the healing process is not conducted in this study.